Virulence factor profile and antibiotic resistance of Escherichia coli O157 strains isolated from animal raw meat - Lotfi, Mandana; Momtaz, Hassan; Tajbakhsh, Elahe (2021)
The current research was done to study the prevalence of antibiotic resistance and distribution of virulence factors amongst the Escherichia coli O157 strains isolated from 180 animal raw meat samples (60 chicken, 30 camel, 40 bovine, 30 turkey, and 20 ovine). E. coli O157 strains harbored the highest prevalence of resistance against tetracycline (94.4%), trimethoprim (61.1%), co-trimoxazole (55.5%), and gentamicin (55.5%) antibiotics. The most commonly detected virulence factors amongst the E. coli O157 isolates were fimH (88.8%), papC (61.6%), cnf1 (61.6%), afa/draBC (61.6%), papGII (55.5%), csgA (55.5%), and cvaC (55.5%). Findings exhibited that all bovine, ovine, caprine, and camel meat samples can be reservoirs of the virulent and antibiotic resistant E. coli O157 strains. Simultaneous presence of some virulence factors together were found in several E. coli O157 strains which showed their high pathogenicity. Retail ruminant meat may be reservoirs of
virulent and resistant E. coli O157 strains.
Keywords: Resistance to antibiotics; Escherichia coli